(untitled) (Research, Society and Development, 2021)
There were several impacts, studies and discussions about the challenges faced exclusively by teachers who work in the early years of elementary school in times of the COVID-19 pandemic. From the relevance of these impacts comes the motivation for the present research, which aimed to understand and discuss the didactic-pedagogical difficulties encountered by teachers of the early years of elementary school in a state public school in Juína-MT, when using the Microsoft Teams® platform to teach classes during the COVID-19 pandemic in 2020. The investigation can be characterized as a case study with a qualitative approach. For the production of data, a questionnaire with open questions and observations was used, directed to teachers from the 1st to 5th grade of a public school in Juína-MT. Data analysis was performed according to Laurence Bardin’s content analysis. The results show that the Microsoft Teams® platform was unknown to all the teachers involved in the research, thus emerging as a challenge with regard to the development of classes. The main challenges highlighted by the participants were: difficulties in handling the new platform, precarious internet network, scarce student participation and lack of interest, little family involvement in the children’s school process, in addition to the students’ lack of technological resources, showing great social inequality of access. There was also a moment of insecurity in the use of the referred platform because it was something new for everyone, and the “new” often brings out the insecurity expressed in the words of the participants. Therefore, during the year 2020, in the context of the COVID-19 pandemic, participants needed to spend more time together and overcome challenges of technological, training nature and problems with the access to technological resources essential for the smooth running of remote education.